1993
DOI: 10.1364/ao.32.004088
|View full text |Cite
|
Sign up to set email alerts
|

Scattering by aggregates with and without an absorbing mantle: microwave analog experiments

Abstract: We present angular scattering functions for loosely packed aggregates of 250 and 500 identical spheres near the Rayleigh size limit before and after the application of successive layers of an absorbing mantle. All measurements were obtained by using the microwave analog technique. Gross features of the scattering by aggregates without a mantle can be interpreted in terms of coherent scattering from the unit spheres acting independently of each other. The largest deviations from this approximation occur after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 10 publications
3
9
0
Order By: Relevance
“…The DOPE experiment (Combet et al 2000) studies compact particles of different materials but their nickel samples can be considered as aggregates in terms of their structure. The most comparable experimental work uses microwave analogs (Zerull et al 1993, Gustafson andKolokolova 1999). All these works deal with particles smaller than in the present work; nevertheless, the comparison could help to understand remote observations.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The DOPE experiment (Combet et al 2000) studies compact particles of different materials but their nickel samples can be considered as aggregates in terms of their structure. The most comparable experimental work uses microwave analogs (Zerull et al 1993, Gustafson andKolokolova 1999). All these works deal with particles smaller than in the present work; nevertheless, the comparison could help to understand remote observations.…”
Section: Discussionmentioning
confidence: 93%
“…Their result is similar to those of Xing and Hanner (1997) for a mixture of tetrahedral aggregates of silicate and carbon. Using the microwave analog technique, Zerull et al (1993) studied fluffy aggregates with carbon mantles. When the mantle on the silicate grains is thin, P max decreases, and it increases when the mantle become thicker.…”
Section: Polarization Branch At Maximum (α Near 90-100mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, this phase information was never exploited to its full potential and measurements were almost always restricted to co-polarized or total intensities [4,5,6,7,8]. Furthermore, the types of targets studied were predominantly either complex (but not controlled [4,5,7,8]), or controlled (but regular [6,9]). Hence it became desirable to extend those measurements to complex targets with fully known geometrical properties, and at the same time analyze the phase of the scattered fields for all (co-and cross-) polarizations.…”
Section: Introductionmentioning
confidence: 99%
“…West (1991) and Zerull et al (1993) have demonstrated both by computations and laboratory measurements that scattering properties of an aggregate particle are strongly influenced by the scattering properties of its individual constituent particles. This important result means that the optical properties of nonspherical particles comparable in size to the wavelength of light have to be understood before modeling cometary dust as aggregate particles.…”
Section: Introductionmentioning
confidence: 99%